Democratic communities: evaluating trialogue for mental health stakeholders. Issue 2 (17th May 2018) - MacGabhann, Liam; Dunne, Simon; McGowan, Paddy; Amering, Michaela
Abstract : Purpose: The purpose of this paper is to evaluate the usefulness of the first Trialogue Meetings throughout Ireland for individuals from mental health communities by using a participatory action research (PAR) framework. Design/methodology/approach: Seven communities participated in monthly Trialogue Meetings as a community-based PAR project. A mixed-methods PAR evaluation was performed on data from 48 participants (service users, service providers, family members/friends and interested community members) who participated in the final Trialogue Meetings. Findings: Participants identified that Trialogue increased knowledge/awareness of mental health, irrespective of gender, mental health role, age or employment status. Trialogue Meetings provided a supportive environment for many, where men may be comfortable talking and where service providers may benefit from exposure to broader perspectives on mental health. Participants also perceived that Trialogue Meetings deconstructed pre-existing mental health power structures, allowed them to understand mental health from different perspectives and express themselves better. Research limitations/implications: The study identifies barriers to Trialogue efficacy such as low service provider engagement and political dynamics extraneous to the meetings themselves. Practical implications: Where desirable conditions are present, Trialogue Meetings appear to be sustainable community development initiatives where pre-existing mental health power dynamics may be levelled and knowledge/communication surrounding mental health may be enhanced. Originality/value: This is the first large-scale evaluation of the innovative Trialogue method among mental health stakeholders using a PAR approach.